2012
DOI: 10.1021/ja212054e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization with a Water-Soluble Rigid Biradical

Abstract: A new biradical polarizing agent, bTbtk-py, for dynamic nuclear polarization (DNP) experiments in aqueous media is reported. The synthesis is discussed in light of the requirements of the optimum, theoretical, biradical system. To date, the DNP NMR signal enhancement resulting from bTbtk-py is the largest of any biradical in the ideal glycerol/water solvent matrix, ε = 230. EPR and X-ray crystallography are used to characterize the molecule and suggest approaches for further optimizing the biradical distance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
104
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 31 publications
3
104
0
Order By: Relevance
“…In contrast to trityl, for which there are very few protons near the radical center, the SA-BDPA molecule has 14-17 protons with large hyperfine couplings. 7 Hovav et al predict the splitting of the DNP matching condition due to the electron-nuclear couplings of nearby nuclei, 36 as do we in (6). When comparing the trityl and SA-BDPA fre- quency sweeps, we see that this effect is clearly demonstrated here.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In contrast to trityl, for which there are very few protons near the radical center, the SA-BDPA molecule has 14-17 protons with large hyperfine couplings. 7 Hovav et al predict the splitting of the DNP matching condition due to the electron-nuclear couplings of nearby nuclei, 36 as do we in (6). When comparing the trityl and SA-BDPA fre- quency sweeps, we see that this effect is clearly demonstrated here.…”
Section: Resultssupporting
confidence: 69%
“…We further note that the observation of higher order transitions for n = 2, 3, 4 indicates that it is possible that similar high order transitions contribute to DNP at the usual, n = 1, condition. For example, if three nuclei and one electron begin in the state |S α I j, α I k, α I l, β , then all spins can be inverted, yielding the final state |S β I j, β I k, β I l, α , and having a transition frequency of ω S ≈ ω 0, I , according to (6). Thus, this would be observed at the n = 1 condition, although the transition itself involves three nuclear spins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumata et al (18,19) have shown that precipitation can be used for 1,3 bisdiphenylene-2-phenylallyl (BDPA) and 2,2 diphenyl-1-picrylhydrazyl (DPPH). For TEMPO, with its derivatives including most currently used biradicals (20)(21)(22)(23)(24)(25)(26), we have Significance Hyperpolarization by dissolution dynamic nuclear polarization can dramatically enhance signal intensities in MRI and NMR, notably for metabolic tracers for imaging and diagnosis. It is applicable to a variety of substrates for in vivo imaging and chemistry but requires the use of contaminants (glassing agents and free radicals) that may interact with cells and proteins and can have potential side effects.…”
mentioning
confidence: 99%
“…The DNP enhancement can be achieved by the addition of stable radicals such as TOT-APOL to the solvent (Song et al 2006), by covalent grafting of such radicals to the proteins , and by saturating the EPR transitions with a powerful microwave source such as a gyrotron (Hall et al 1997). Sensitivity enhancements on the order of e on/off * 200 (i.e., the ratio of signal intensities obtained with and without microwave irradiation) have been observed in frozen glycerol/water matrices at temperatures in the vicinity of 100 K (Kiesewetter et al 2012), resulting in a reduction of experimental times by a factor of (e on/off ) 2 = 40,000 allowing this approach to be applied to a variety of molecular systems beyond the reach of traditional methods. For example, applications to surface science (Vitzthum et al 2012;Zagdoun et al 2012;Lelli et al 2011) have been remarkably successful and may open the way to improved understanding of heterogeneous catalysis and other phenomena that can only occur on surfaces.…”
Section: Introductionmentioning
confidence: 99%